Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1063/1.1408591
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of GaN quantum dots by ion implantation in dielectrics

Abstract: GaN nanocrystals (in the wurtzite phase) were synthesized by sequential implantation of Ga and N ions into either crystalline (quartz, sapphire) or amorphous (silica) dielectrics, followed by annealing of the samples in flowing NH3 gas at 900 degreesC. GaN was formed by reaction of implanted Ga with NH3 combustion products and/or via conversion of Ga oxide/oxynitrides. A blueshift of the near-band-edge photoluminescence (quantum-confinement effect) was observed for GaN nanocrystals with size less than or equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 19 publications
1
32
0
1
Order By: Relevance
“…[2] Gallium nitride (GaN) is a widely used III-V semiconductor in micro-and optoelectronic devices, such as blue light-emitting diodes and lasers. GaN quantum structures (or nanodots) have received particular attention for potential applications in lightemitting diodes [3,4,5] and high-temperature electronic devices. [2] GaN nanodots have been synthesised experimentally by various methods, including colloidal dispersion, [6] ion implantation, [7,4] molecular beam epitaxy, [5] and metal-organic chemical vapour deposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Gallium nitride (GaN) is a widely used III-V semiconductor in micro-and optoelectronic devices, such as blue light-emitting diodes and lasers. GaN quantum structures (or nanodots) have received particular attention for potential applications in lightemitting diodes [3,4,5] and high-temperature electronic devices. [2] GaN nanodots have been synthesised experimentally by various methods, including colloidal dispersion, [6] ion implantation, [7,4] molecular beam epitaxy, [5] and metal-organic chemical vapour deposition.…”
Section: Introductionmentioning
confidence: 99%
“…GaN quantum structures (or nanodots) have received particular attention for potential applications in lightemitting diodes [3,4,5] and high-temperature electronic devices. [2] GaN nanodots have been synthesised experimentally by various methods, including colloidal dispersion, [6] ion implantation, [7,4] molecular beam epitaxy, [5] and metal-organic chemical vapour deposition. [8] One of the most notable aspects of quantum confinement in semiconductors is the nanostructure size dependence of the band gap; namely, the band gap increases as the size decreases.…”
Section: Introductionmentioning
confidence: 99%
“…A number of nanocrystalline GaN studies were reported through some grown techniques (Mićić et al 1999;Borsella et al 2001;Miyamura et al 2002;Zhuang et al 2013;Gyger et al 2014). GaN quantum dots were grown by Miyamura et al (2002) through low-pressure metalorganic chemical vapor deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Two blue-shifted PL peaks were observed at 4.18 and 3.59 eV for two different quantum dot structures. Hexagonal nanocrystalline GaN with the size of 2-3 nm was generated by Borsella et al (2001) via sequential Ga and N ions implantation into crystalline and amorphous dielectrics tracked by annealing of the samples GaN in flowing ammonia gas at 900°C. Recently, quantum-confined cubic GaN nanoparticles with the size of 3-4 nm have been synthesized by Gyger et al (2014) via liquid-ammonia-in-oil-microemulsions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature on GaN ion synthesis in silicon or in Si-compatible matrices is almost absent. Only one research group [7,8] has reported on the synthesis of light-emitting GaN crystallites in SiO 2 and Al 2 O 3 matrices after co-implantation of gallium and nitrogen ions and subsequent annealing in ammonia atmosphere.…”
Section: Introductionmentioning
confidence: 99%